(3GdNOeI GdYehejI GdeMdjI ceDTQ ddJfejI GdeSJOGeIs - (3fhQ GdOjf(B, (3MGQhTs; (3QeVGf RHjQj hBNQhf(B, s ((3GdLRGFQ(B:s (3OGQ GdCeI ddfTQ hGdJhRjY(B,s, 2017)
(3CSS GdJfXje GdEOGQj hGdEOGQI GdeMdjI,GdSjGSI hGdMcGeI GdeMdjI hYdGbJgG HGdNOeI GdYehejI,eMJhjGJ GdJfejI GdeSJOGeI heDTQGJ bjGSgG,eSJhjGJ GdJfejI GdeSJOGeI hOhQ GdJfejI GdeMdjI ajgG,OhQ GdeJZjQGJ GdOjeZQGajI aj GdJfejI GdeMdjI,JfejI GdeLJeY GdMVQj hGdeSJMOK,GdJfejI GdeMdjI HGdeLJeY GdQjajs
(3HHdjhZQGajG(B: (3U(B.237-250s
Keywords: (3GdGOGQI GdeMdjIs